Activated Carbon from Corncobs Doped with RuO2 as Biobased Electrode Material - Viola Hoffmann; Catalina Rodriguez Correa; Saskia Sachs; Andrea del Pilar Sandoval-Rojas; Mo Qiao; Avery B. Brown; Michael Zimmermann; Jenny Paola Rodriguez Estupiñan; Maria Teresa Cortes; Juan Carlos Moreno-Piraján; Maria-Magdalena Titirici; Andrea Kruse (Electronic Materials, 2021)
Bio-based activated carbons with very high specific surface area of >3.000 m² g−1 (based on CO2 adsorption isotherms) and a high proportion of micropores (87% of total SSA) are produced by corncobs via pyrolysis and chemical activation with KOH. The activated carbon is further doped with different proportions of the highly pseudocapacitive transition metal oxide RuO2 to obtain enhanced electrochemical properties and tune the materials for the application in electrochemical double-layer capacitors (EDLC) (supercapacitors). The activated carbon and composites are extensively studied regarding their physico-chemical and electrochemical properties. The results show that the composite containing 40 wt.% RuO2 has an electric conductivity of 408 S m−1 and a specific capacitance of 360 Fg−1. SEM-EDX, XPS, and XRD analysis confirm the homogenous distribution of partly crystalline RuO2 particles on the carbon surface, which leads to a biobased composite material with enhanced electrochemical properties.